2015
DOI: 10.1007/s00264-015-2920-6
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of bionic, screw and Endobutton fixation in the treatment of tibiofibular syndesmosis injuries

Abstract: The bionic fixation at least equals the performance of Endobutton fixation; it also allows more physiologic movement of the syndesmosis when compared to the screw fixation and may serve as a viable option for the fixation of the tibiofibular syndesmosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
0
22
1
Order By: Relevance
“…Several groups have previously modified suture button devices 30 or implementation of such devices 32 with the intention of improving mechanical function, particularly in the sagittal plane. However, as was also determined in our work, modified flexible fixation devices tend to result in biomechanics similar to those of commercially available suture button constructs implemented according to manufacturer guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have previously modified suture button devices 30 or implementation of such devices 32 with the intention of improving mechanical function, particularly in the sagittal plane. However, as was also determined in our work, modified flexible fixation devices tend to result in biomechanics similar to those of commercially available suture button constructs implemented according to manufacturer guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…However, as was also determined in our work, modified flexible fixation devices tend to result in biomechanics similar to those of commercially available suture button constructs implemented according to manufacturer guidelines. 30 The metallic augmentation of the prototype suture button device used in this work was intended to address complications such as bone tunnel erosion rather than to modify device mechanics. Though no evaluation of long-term bone tunnel erosion could be performed in this cadaveric study, the biomechanical similarity in rotational stability of the prototype device compared to the suture button group indicated that the prototype design was functionally very similar to existing methods for syndesmotic repair.…”
Section: Discussionmentioning
confidence: 99%
“…The distal tibiofibular syndesmosis comprises 2 bones and 4 ligaments and is a delicate structure. It provides a dynamic relationship for the tibia and fibula during ankle motion (19,20). The main treatment of distal tibiofibular syndesmosis injury includes conservative care and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Some limited investigations have attempted to compare dynamic suture button fixation with syndesmotic screw fixation [54,[57][58][59][60][61][62]. Westermann et al performed a cadaveric study to see if there was a difference in the malreduction of syndesmotic injuries when comparing screw fixation with tightrope fixation [58].…”
Section: Operative Treatment For Isolated Syndesmotic Injuriesmentioning
confidence: 99%